Pengaruh Material yang Berbeda Terhadap Laju Perpindahan Panas - Jamilah Jamilah Jamilah; Fadhila Rahma Oktavia; Salsabila Widya Nafita (Jurnal Penelitian Fisika dan Terapannya (JUPITER), 2021)
This research is based on material differences that greatly affect heat transfer. The purpose of this study is to determine the rate of heat transfer that occurs in different materials. The method of research conducted is to use the experimental method by preparing glasses of glass and plastic (with a size of 200 ml) then filled with hot water that will be observed temperature changes every 5 minutes with 1 thermometer alternately. The results of this study showed that objects with high conductivity (glass glasses) have a slower rate of temperature drop than objects with low conductivity materials (plastic cups) have a faster rate of temperature drop.Keywords : Conductivity, Heat transfer,Temperature.